Efeito residual de fipronil sobre Apis mellifera L. (Hymenoptera: Apidae) Africanizada - Ribeiro, Leticia da Silva (2023)
Among the essential pollinators for the maintenance and conservation of biodiversity in ecosystems, the bees Apis mellifera L. (Hymenoptera: Apidae) play a major role. However, the mortality of this insect is causing concern. Thus, the objective of this work was to evaluate the residual effect of the insecticide fipronil on A. mellifera africanized by contact on a contaminated surface. The evaluation of the residual effect of fipronil was verified in three bioassays. In Bioassay 1, without photodegradation action, about 290 microliters of five concentrations (0.75 µg/mL; 1.5 µg/mL; 3 µg/mL; 6 µg/mL and 12 µg/mL) were sprayed on plates of glass petri. In bioassay 2, with the action of photodegradation, about 290 microliters of the average lethal concentration in 48 hours (LC50 48h) of 5 mg/mL was also sprayed on glass petri dishes. The application of the 48h CL50 occurred in two groups: with and without photoperiod, both kept under controlled conditions. For both bioassays, the controls consisted of glass petri dishes sprayed with sterilized distilled water. The contact of the bees with the plates of both bioassays occurred for a period of 2 hours. After this period, the bees were relocated in cages and transferred to a climate-controlled room, being evaluated periodically, from 1 to 120 hours after contact. In Bioassay 3, the activity of the enzyme acetylcholinesterase (AChE) of bees after interaction with the insecticide fipronil was verified. For this, the bees were placed in contact with the CL50 24h and 48h for 4, 24 and 48 hours. After the contact period, the bees were stored in an ultrafreezer at -80ºC. The second group of bees that was in contact with the treatment with CL50 24 and 48 h for 24 and 48 hours was also frozen after this period of contact. The action of fipronil in bioassays 1 and 2 reduced the survival of A. mellifera when in contact with a contaminated surface, as well as when left in an environment without photoperiod (light). In bioassay 3, it was verified that the insecticide fipronil did not cause biochemical alterations in the AChE enzyme. In this way, it is recommended to carry out more studies evaluating the enzymatic activity in a longer time, after the bees come into contact with the product.